Peningkatan Cyber Security dan Penggunaan Sosial Media dalam Teknologi Informasi di Era Digital di SMK Media Informatika - Muhamad Firly; Muhamad Ridwan Nurrulloh; Maulana Farras Fathurrahman; Abdul habib Hasibuan (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
This community service program aims to improve the knowledge and skills of students at SMK Media Informatika in cybersecurity and responsible use of social media in the digital age. The training consisted of interactive sessions covering fundamental information security concepts, awareness of cyber threats, and ethical social media practices. Evaluation results indicated significant improvements in students’ understanding, threat recognition skills, and responsible social media conduct. Furthermore, the training effectively raised awareness of digital security within the school and positively influenced students’ daily behavior. It isrecommended to integrate cybersecurity and social media literacy topics into the curriculum and to conduct ongoing training programs to continuously enhance student competencies.